2018
DOI: 10.1073/pnas.1721245115
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting LXRα phosphorylation promotes FoxM1 expression and modulates atherosclerosis by inducing macrophage proliferation

Abstract: Macrophages are key immune cells for the initiation and development of atherosclerotic lesions. However, the macrophage regulatory nodes that determine how lesions progress in response to dietary challenges are not fully understood. Liver X receptors (LXRs) are sterol-regulated transcription factors that play a central role in atherosclerosis by integrating cholesterol homeostasis and immunity. LXR pharmacological activation elicits a robust antiatherosclerotic transcriptional program in macrophages that can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 55 publications
(66 reference statements)
4
36
0
Order By: Relevance
“…Our findings complement a recent elegant study by Gage et al that demonstrated a myeloid-specific knock-in of LXRa S196A resulted in greater macrophage proliferation via the LXRa S196A dependent upregulation of FOXM1, and increased atherosclerosis (17). The difference in the phenotypes between the myeloid-specific expression of S196A versus our bone marrow transplant model, in which the entire complement of hematopoietic cells express LXRa S196A suggest that LXRa S196A expression within additional bone marrow-derived cells restrain In summary, we showed that reducing LXRa pS196 in bone marrow cells of Ldlr -/mice reduced VAT weight and attenuated atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings complement a recent elegant study by Gage et al that demonstrated a myeloid-specific knock-in of LXRa S196A resulted in greater macrophage proliferation via the LXRa S196A dependent upregulation of FOXM1, and increased atherosclerosis (17). The difference in the phenotypes between the myeloid-specific expression of S196A versus our bone marrow transplant model, in which the entire complement of hematopoietic cells express LXRa S196A suggest that LXRa S196A expression within additional bone marrow-derived cells restrain In summary, we showed that reducing LXRa pS196 in bone marrow cells of Ldlr -/mice reduced VAT weight and attenuated atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…C57BL/6 LXRa S196A mice were generated by Ozgene, and have been described (17,19 sucrose/saline. Organs weight was measured.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences likely lead to cell-type specific responses to LXR activation. To identify potential T cell specific LXR targets we cross-referenced our list of DEGs with two publically available RNA-sequencing datasets from murine macrophages (mMφ) treated with GW 21,22 . Of the DEGs identified in T cells, 52% were similarly regulated in mMφ, and remarkably, 29% were uniquely regulated in the T cell dataset (Fig.…”
Section: Lxr Transcriptionally Regulates Lipid Metabolic Pathways Inmentioning
confidence: 99%
“…Macrophages are phagocytic leukocytes of the innate immune system 21 that play significant direct and indirect roles in the progression of diabetes and atherosclerosis through their ability to secrete a wide array of potent inflammatory cytokines, proliferate in situ 22 and take up modified LDL in the arterial wall 23 . While the effects of insulin resistance in metabolic tissues in atherosclerosis are well defined [4][5][6] , the effects of insulin resistance in macrophages are less clear and often conflicting [10][11][12][18][19][20] , which may be due to a lack of consistency with the models used and end points measured.…”
Section: Introductionmentioning
confidence: 99%